MORFOLOGI GENDER DALAM BAHASA ARAB DAN INGGRIS (ANALISIS KONTRASTIF DALAM FUNGSI PENGAJARAN BAHASA ARAB) - Ardiansyah Ardiansyah (AT-TURATS, 2017)
This research purposes is to explain gender mark lingual units whether in Arabic or English on morphology level addressed to language pronounciation. Contrastive analysis results can be used to understand Arabic gender by making english as language connections. The data taken from relevant dictionaries because it is one of written language container. The data proceed using three stages : data supply, data analysis and data analysis results supply. On analysis stage: this research using contrastive methods. This research conclusion that both languages have more diffences than similarities. Arabic has dominated by bound morpheme while English has dominated by free morpheme or lexical.